Water effects on Body-Centric communication radio channel - Al-Saffar, Dina; A. Hammas, Hussain (International Journal of Electronics and Telecommunications, 2026)
Nowadays, the trend in communication technology is gathering clothing with electronic technology. There are two factors despite each others, the convenient of On-Body antennas power supply on the cloth and the power combined with the biological lossy tissues for the human; therefore, efficiency is important when considering Body-Centric communication systems. In this work, the experiments conducted in the study of Off-Body radio with water in the channel are described. To manage the searching properties of water two techniques were studies. The first was a simulation of multilayeres human model with and without a water layer in aspect of transmission coefficient and antenna reflection, the second was to use a gel to absorb water, Polyacrylamide, within special box underneath the On -Body antenna measuring the s11 in frequency 2.1 GHz